STAPHYLO COCCUS PSEUDINTERMEDIUS ISOLATION FROM CANINE, BACTERIAL COLONIZATION AND CLINICAL PICTURE IN BALB/C MOUSE MODEL - D. H. Kalhoro; S. Gao; M. S. Kalhoro; F. Parveen; M.Tariq; S.A. Pirzado; Y. J. Liu1 (Journal of Animal and Plant Sciences, 2017)
Staphylococcus pseudintermedius is an emerging pathogen causing respiratory infection in dogs. In this experiment pathogenicity characteristic of S. pseudintermedius were determined. The research was mainly focused on three aspects including bacterial load, histopathological changes and virulence factors. BALB/c mice were intranasaly inoculated with S. pseudintermedius. The results showed that the bacteria can cause serious neurologic symptoms including walking in circles, bending of neck and produces obvious histopathological changes in lung and brain of the mice. In lungs and brain higher levels of bacterial load was observed during present study. Of all 11 oxacillin-resistant isolates of S. pseudintermedius, 2 carried SCCmec types II–III, 2 carried SCCmec I and 3 carried SCCmec types III according to PCR-based SCCmec typing. Exfoliative toxin (siet), lukS and luk F genes were also identified from the isolates.
Keywords: Staphylococcus pseudintermedius; Mouse model; Bacterial load; Histopathology; Virulence factors